Patients’ perception about opioids and addiction in South Korea - Kim, Cho Long (Korean J Pain, 2020)
BACKGROUND: Chronic pain affects approximately 22% of the world’s population. Opioids can be useful in chronic pain management. However, some patients have negative perception of opioids. The purpose of this research was to evaluate patients’ perception about opioids and investigate problems associated with prescribing and taking opioids in South Korea. METHODS: Patients who visited a pain clinic in 14 university hospitals of South Korea from September through October 2018 were asked to complete anonymous questionnaires about taking opioids. RESULTS: Of the 368 patients that were surveyed (female 53.3%, male 46.7%), 56.8% were prescribed opioids. In the opioid group, 92.8% patients had heard of opioids from their doctor and 72.6% of them had a positive perception about opioids. The side effects associated with opioid use were constipation (35.4%), dizziness (24.6%), nausea and vomiting (17.4%), dysuria (6.2%), and addiction (2.0%). In the no opioid group, the primary sources of information about opioids were doctors (49.2%), mass media (30.8%), and the internet (16.2%). The main reasons why 39.0% patients did not take opioids were fear of addiction (57.7%) and side effects (38.5%). There were 71.5% and 60.9% patients in the opioid and no opioid group, respectively, who wished to take opioids when their numeric rating scale pain score was ≥ 7. CONCLUSIONS: Perception of opioids among patients who take them was either neutral or positive. However, 39.0% patients who have not been prescribed opioids did not want an opioid prescription, citing fear of addiction and side effects as the primary reasons.